Epidemiological Characteristics of Death by Covid-19 in Brazil in the year 2020 (Research, Society and Development, 2022)
The Covid-19 Pandemic exposed an International Conjuncture marked by a growing concern about the need to establish health protocols for the proper management of the established crisis. In Brazil, this pandemic was marked by the lack and inequality of access to hospital supplies and the lack of control of sanitary measures, in addition to the fact that there is a strong context of social inequality in the country. Thus, the present study aims to analyze the profile of deaths by Covid-19 in the five Brazilian regions, highlighting the conditions that potentiate the disease. Data were obtained from a National Database - SRAG 2020, and information was collected on 174,059 patients who died from Severe Acute Respiratory Syndrome (SRAG) resulting from Covid-19, which occurred during 2020. It was observed that of the 174,059 deaths, most were male, most occurred in the Southeast region, and the most prevalent age groups were 70 to 79 years, 60 to 69 years, and 80 to 89 years. As for the most recurrent signs/symptoms and pre-existing diseases, we have: Dyspnea, Cough, Oxygen Saturation (SatO2) < 95%, Respiratory Discomfort, Heart Disease, Diabetes, Systemic Arterial Hypertension, Kidney Pathologies, Neurological Diseases, Pneumopathy Chronic and Obesity. There is an important relationship between mortality caused by Covid-19 and the occurrence of some variables, such as advanced age, male gender and the presence of some preexisting diseases, especially the following: Chronic Cardiovascular Disease, Diabetes mellitus, Systemic Arterial Hypertension.